Fabrication of magnetite nanoparticles/polyvinylpyrrolidone composite nanofibers and their application as electromagnetic interference shielding material. (April 2018) - Nasouri, Komeil; Shoushtari, Ahmad Mousavi
Magnetite (Fe3 O4 ) nanoparticles/polyvinylpyrrolidone (PVP) composite nanofibers (FCNFs) have been fabricated to evaluate the potential of FCNFs as electromagnetic interference (EMI) shielding material in the frequency range of 8.2–12.4 GHz. The scanning electron microscope and viscosity analyses confirmed the presence of good dispersion Fe3 O4 nanoparticles encapsulated within the electrospun nanofibers and showed FCNF morphologies with diameters of 150–500 nm. The magnetic properties and electrical conductivity of FCNFs were found to be dependent on Fe3 O4 nanoparticles concentration and showed an increase with increasing Fe3 O4 nanoparticles loading. The EMI shielding efficiency of FCNFs increased up to approximately 22 dB. The EMI shielding results for FCNFs showed that absorption was the major shielding mechanism and reflection was the secondary shielding mechanism. The present study has shown the possibility of utilizing magnetic FCNFs as EMI shielding/absorption materials.